Minimum Information Required to Annotate Food Safety Risk Assessment Models (MIRARAM). (January 2021) - Filter, Matthias; Sundermann, Esther M.; Mesa-Varona, Octavio; Buschhardt, Tasja; Lopez de Abechuco, Estibaliz; Georgiadis, Marios
Graphical abstract: Highlights: Food safety risk assessment models sometimes lack important metadata. Guidelines on how to annotate models in a harmonized way could assist in a more efficient exchange, re-use and continuous improvement of the models. Proposed MIRARAM guideline builds on best practices from related disciplines. Adoption of MIRARAM will facilitate model re-use. Abstract: In the last decades, mathematical models and model-based simulations became important elements not only in the area of risk assessment concerning microbiological and chemical hazards but also in modelling biological phenomena in general. Unfortunately, many of the developed models are published in non-standardized ways, which hinders efficient exchange, re-use and continuous improvement of models within the risk assessment domain. The establishment of guidelines for model annotation is an important pre-condition to overcome these obstacles. Additionally, implementation of annotation guidelines can improve transparency, quality control and even aid the clarification of intellectual property rights. Here, we address the question of "What is the minimum set of metadata that should be provided for a model in the risk assessment domain?". The proposed guideline focuses on food safety risk assessment models and is called "Minimum Information Required to Annotate food safety Risk Assessment Models (MIRARAM)". MIRARAM supports the model creator during the model documentation step and could also be used as a checklist by scientific journal editors or database curators. Software developers could take up MIRARAM and develop easy-to-use software tools or new features in existing programs that can help model creators to provide proposed model annotations in harmonized file formats. Based on experiences from similar guidelines in related scientific disciplines (like systems biology), it is expected that MIRARAM could contribute to the promotion of application and re-use of models as well as to implementing more standardized quality control in the food safety modelling domain.